The Effect of Capital Structure and Company Size on Bonds in Pharmaceutical Companies listed on IDX in 2020 - 2023 - Nehru Rizki Achrommico; Indra Wijayanto; Yanna Eka Pratiwi; Siwidyah Desi Lastianti; Ida Budiarti (Lembaga Riset dan Inovasi Al-Matani, 2025)
This research uses a qualitative method with an explanatory causality approach to see and examine the cause-and-effect relationship between variables, which includes the variables of capital structure, company size, and bonds. The purpose of this study is to analyze the effect of capital structure and company size on bond issuance in pharmaceutical companies listed on the IDX from 2020 to 2024. The results of this study indicate that capital structure has a positive but insignificant effect on bond issuance. Company size also shows a positive but insignificant effect. Large companies do have a greater capacity to issue bonds. Simultaneously, capital structure and firm size do not significantly affect bond issuance. These findings contribute to understanding the internal dynamics of companies in making funding decisions, especially related to bond issuance, and can be a reference for company management and investors in making strategic decisions in the future.